Influence of multiwalled carbon nanotubes on biodegradable Poly(lactic acid) nanocomposites for electroactive shape memory actuator - Mohan, Raja; Subha, J.; Alam, Javed; Ali, Fathilah (Wiley, 2016)
Poly(lactic acid)/epoxidized soybean oil/carbon nanotubes (PLA/ESO/CNTs) nanocomposites were prepared by the solution blending process, and the influence of ESO on the properties of the composites was studied. Differential scanning calorimetry and X-ray diffraction revealed that the addition of CNTs improved the crystallinity of the nanocomposites. The modulus increased with the addition of CNTs content in the composites. Morphological characterizations were done by scanning electron microscopy and transmission electron microscopy. Electrical conductivity of PLA/ESO/CNT composites increased with the addition of CNTs. This study revealed that the addition of ESO facilitated the dispersion of the CNTs in the PLA matrix.